Measurement of the Z+b-jet cross-section in pp collisions at √s = 7 TeV in the forward region - Aaij, Roel; Adeva, B.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Journal of high energy physics, 2015)
The associated production of a Z boson or an off-shell photon γ*with a bottom quark in the forward region is studied using proton-proton collisions at a centre-of-mass energy of 7 TeV. The Z bosons are reconstructed in the Z/γ*→ μ+μ−final state from muons with a transverse momentum larger than 20 GeV, while two transverse momentum thresholds are considered for jets (10 GeV and 20 GeV). Both muons and jets are reconstructed in the pseudorapidity range 2.0 < η < 4.5. The results are based on data corresponding to 1.0 fb−1 recorded in 2011 with the LHCb detector. The measurement of the Z+b-jet cross-section is normalized to the Z+jet cross-section. The measured cross-sections are σ(Z/γ∗(µ+µ−) + b-jet) = 295 ± 60 (stat) ± 51 (syst) ± 10 (lumi) fb (0.1) for pT(jet) > 10 GeV, and σ(Z/γ∗(µ+µ−) + b-jet) = 128 ± 36 (stat) ± 22 (syst) ± 5 (lumi) fb (0.2) for pT(jet) > 20 GeV.
Im Titel steht "s" unter dem Wurzelzeichen
Gesehen am 05.10.2020
The LHCb Collaboration: R. Aaij, B. Adeva, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov, l. Zhong, [und 663 weitere]